1988
DOI: 10.1159/000234599
|View full text |Cite
|
Sign up to set email alerts
|

Retained T-Cell Reactivity of Rye Grass Pollen Extract following Cleavage with Cyanogen Bromide and Nitrothiocyanobenzoic Acid

Abstract: Rye grass pollen extract was fragmented by sequential treatments with cyanogen bromide and 2-nitro-5-thiocyanobenzoic acid, and a fraction containing fragments of molecular weight greater than 10,000 Mr was isolated. The in vitro reactivity of the extract with specific IgE was extensively reduced by fragmentation. Less reduction in activity was shown either by skin testing or by inhibition of an extract-specific IgG-binding assay. Reactivity with, and ability to induce, extract-specific mouse T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…A simi lar observation has been reported for the tryptic pep tides TM1 and TM2 of cod allergen M. In the RAST assays, these peptides inhibited the binding of al lergen M to human serum IgE antibodies offish aller gic individuals to the extent of approximately 85% [1,2]. On the other hand, the results of the present study are in contrast to recent reports [13,14] where the authors observed a major reduction in the capacity of a crude ryegrass pollen extract to bind human IgE antibodies after cleavage of the crude extract with CNBr and nitromiocyanobenzoicacid. However, a direct comparison between these studies is not possible since our experiments were performed with a highly purified allergen and not the crude pollen extract.…”
Section: Discussionsupporting
confidence: 56%
“…A simi lar observation has been reported for the tryptic pep tides TM1 and TM2 of cod allergen M. In the RAST assays, these peptides inhibited the binding of al lergen M to human serum IgE antibodies offish aller gic individuals to the extent of approximately 85% [1,2]. On the other hand, the results of the present study are in contrast to recent reports [13,14] where the authors observed a major reduction in the capacity of a crude ryegrass pollen extract to bind human IgE antibodies after cleavage of the crude extract with CNBr and nitromiocyanobenzoicacid. However, a direct comparison between these studies is not possible since our experiments were performed with a highly purified allergen and not the crude pollen extract.…”
Section: Discussionsupporting
confidence: 56%
“…In addition other modified allergens have been described that have extensively reduced IgE-reactivities and, poor IgG-inducing pro perties, but yet have various retained T-cell-stimulating capacities in experimental animals. For example, fragments of RE produced by treatment with cya nogen bromide and thiocyanonitrobenzoic acid were shown to be able to stimulate the production of T cells which could respond to accessory-cell-processed RE [8]. Conjugates of the biologically active peptide f met-leu-phe and allergens had similar properties to the fragments but in addition were shown to induce delayed hypersensitivity in guinea pigs [7], Chymotryptically cleaved fragments of rye extract also induced the development of unmodified allergenspecific T cells which could collaborate to produce DNP-specific antibody from B cells following in vivo transfer and challenge with dinitrophenylated grass pollen extract [9].…”
Section: Discussionmentioning
confidence: 99%
“…Modified RE samples were those described in a number of pre vious publications (table I): polysarcosine-RE [6]; f met-leuphe-RE [7]; chemically (cyanogen bromide and thiocyanonitrobenzoic acid) fragmented RE [8], and enzymatically (chymotrypsin) fragmented RE [9].…”
Section: Modified Allergensmentioning
confidence: 99%
See 2 more Smart Citations